The impact of a newly designed resilience-enhancing programme on parent- and teacher-perceived resilience environment among Health Promoting Schools in Hong Kong. Issue 3 (23rd September 2008) - Wong, M C S; Sun, J; Lee, A; Stewart, D; Cheng, F F K; Kan, W; Ho, M
Abstract : Background: The Health Promoting School (HPS) approach provides a strong foundation to improve students' overall health, including psychological well-being, which has its roots in resilience. The present study evaluates the effectiveness of a resilience-enhancing programme, building on the concept of HPS among a Chinese population. Methodology: All mainstream schools in a socially disadvantaged region of Hong Kong were eligible, and stratified random sampling was used to recruit both HPS as intervention schools and non-HPS as control schools. The participants included teachers and parents of grade 3 and 5 primary and grade 1 secondary school students (aged 8, 10 and 12 respectively). Validated surveys were used to assess resilience scores in both groups of schools before and after a series of resilience-enhancing activities in HPS, and ANOVA was used to compare the score changes between the two groups. Results: Five primary and four secondary HPS and four primary and four secondary non-HPS were recruited, involving 4918 parents and 602 teachers. Among primary and secondary parents, the HPS group did not report a higher score than the non-HPS group. Among secondary teachers, the HPS group showed significantly higher scores than the non-HPS group (p  =  0.023 to < 0.001) Conclusion: The present study is the first to demonstrate the positive synergistic effect of a newly designed resilience-enhancing intervention programme, building on the concept of HPS in schools among secondary teachers in Hong Kong. It was suggested that future initiatives may involve parent networking and school–family collaboration in fostering an even more resilient school environment.